Effects of human needs based on the integration of needs as stipulated in Maqasid Syariah and Maslow’s Hierarchy of needs on zakah distribution efficiency of asnaf Assistance Business Program - Maheran Zakaria; Nur Ain Abdul Malek (Penerbit Universiti Kebangsaan Malaysia, 2014)
This study examines the effects of human needs based on the integration of needs as stipulated in Maqasid Syariah and Maslow’s hierarchy of needs on zakah distribution efficiency. Human needs in this study are evaluated based on the integration of 5 elements of human needs as stipulated in Maqasid Syariah and Maslow’s hierarchy of needs. The elements are religion and self-actualization, physical-self and safety, knowledge and social, family and self-esteem, and finally, wealth and physiology. Approximately 300 sets of questionnaires were sent to zakah recipients of Asnaf Assistance Business Program conducted by Majlis Agama Islam Kelantan (MAIK). From this number, 270 people return their responses. Data were analysed using Structural Equation Modelling of AMOSS 20. The findings indicate that the integration of 5 elements of human needs as stipulated in Maqasid Syariah and Maslow’s hierarchy of needs positively affects zakah distribution efficiency. Hence, the study provides an insight to zakah institutions that the distribution of zakah should not confine to fulfilling recipients’ monetary needs but also on non-monetary needs such as enhancing level of religiosity, fostering socialization, training and motivation as well as uplifting living status.